Performance of the Civil Service Police Unit and the Regional Fire Department of North Morowali Regency - Muhammad Rapi; Suasa; Nia Marsella Kurniawati (Journal of Public Administration and Government, 2023)
In the era of regional autonomy, the function of public services became one of the focuses of attention in improving the performance of local government agencies, especially the fire department and the Civil Service Police Unit, but in reality the performance both of these government agencies was not as expected. This study aims to determine how the performance of the Civil Service Police Unit and the Regional Fire Department of North Morowali Regency. This type of research is descriptive qualitative and the basis of this research is a qualitative research method. Based on the results of the study that the performance of the Civil Service Police Unit and the Regional Fire Department of North Morowali Regency seen from the effectiveness and efficiency, authority and responsibility were quite good. However, in the aspect of employee discipline and initiative, the results are not optimal and need to be addressed, because there are still employees who are not familiar with the applicable rules regarding working time. The reason is that the employees do not come on time because the employees have to take care of household matters, and the motivation of the employees, especially the low honorariums, is due to the very minimal honorary salaries and the lack of human resources and facilities and infrastructure.